The Impact of Image Dimensions toward Online Consumers' Perceptions of Product Aesthetics. Issue 5 (17th June 2016) - Park, Jungkun; Gunn, Frances
ABSTRACT: Marketers and industrial designers devote considerable attention to the visual attributes of products, based on the premise that the visual appearance of products influences consumers' judgments of the products' attributes. This research investigated consumers' perceptions about particular types of innovative products (revolutionary technology‐driven products), with 275 consumers sample purchased from an independent marketing company. To achieve the main goal, interrelations among image of product and aesthetics of product have been examined using structural equation modeling with two psychological moderators: consumer innovativeness and needs for uniqueness. The results of this study provide evidence that individual differences in uniqueness motivation moderated how online consumers' perceptions of a product's image characteristics influenced perceptions of value showing consumers' need for uniqueness was more influential toward perceptions of the product's value than perceptions of functional value. Consequently, these findings expand understanding of the consumer characteristics that respond to perceptions of products' epistemic value.